2016
DOI: 10.1017/s0272263115000509
|View full text |Cite
|
Sign up to set email alerts
|

Language Aptitude and Grammatical Difficulty

Abstract: This study investigates the relationship between foreign language aptitude and the learning of two English structures defi ned as easy or diffi cult to learn. Using a quasiexperimental design, 66 secondarylevel learners of English as a foreign language from three intact classes were provided with four hours of instruction on the passive (a diffi cult structure) and the past progressive (an easy structure). Language aptitude was measured using the LLAMA Aptitude Test (Meara, 2005 ). Language outcomes were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 54 publications
3
36
1
Order By: Relevance
“…We also used principal component analysis to investigate the interrelationships between the different subtests in order to assess Granena's (2013a) assertion of a division in the LLAMA between explicit and implicit aptitude and Skehan's (1998) proposal of three aptitude components (memory, analytic ability, and phonetic encoding). The latter have not been examined for the LLAMA, but LLAMA F has been used as a measure of language analytic ability in several studies (e.g., Yalcin & Spada, 2016;Yilmaz, 2013). We thus conducted two-and three-component principal component analyses in order to look for meaningful patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also used principal component analysis to investigate the interrelationships between the different subtests in order to assess Granena's (2013a) assertion of a division in the LLAMA between explicit and implicit aptitude and Skehan's (1998) proposal of three aptitude components (memory, analytic ability, and phonetic encoding). The latter have not been examined for the LLAMA, but LLAMA F has been used as a measure of language analytic ability in several studies (e.g., Yalcin & Spada, 2016;Yilmaz, 2013). We thus conducted two-and three-component principal component analyses in order to look for meaningful patterns.…”
Section: Discussionmentioning
confidence: 99%
“…The construct of language aptitude has gained increasing attention among scholars of language acquisition and use. A growing number of studies have not only assessed the construct of language aptitude itself and its interaction with different cognitive traits but have also examined the explanatory potential of this cognitive individual difference variable across a wide range of contexts, including instructed language learning, early and late second language (L2) acquisition, heritage language development, and first language (L1) attrition (e.g., Abrahamsson & Hyltenstam, 2008;Bylund, Abrahamsson, & Hyltenstam, 2010Yalcin & Spada, 2016;Yilmaz, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Building on Carroll's aptitude model, LLAMA features not only explicit learning aptitude -associative memory, phonemic coding and grammatical inferencing, but also incidental learning aptitude -sound sequence recognition. According to previous investigations, explicit LLAMA test scores appeared to predict the extent to which L2 learners can benefit from explicit (rather than implicit) instruction within a short amount of time under laboratory (e.g., Yilmaz & Granena, 2016) and classroom (e.g., Yalçın & Spada, 2016) conditions. In contrast, L2 learners with high-level incidental aptitude (sound sequence recognition) tend to attain advanced proficiency in L2 morphosyntax, especially when they have had regular access to naturalistic language input since an early age (e.g., Granena, 2013).…”
Section: Second Language Learning Aptitudementioning
confidence: 92%
“…The LLAMA adopts the same measures as in the MLAT for assessing intentional learning abilities (i.e., phonemic coding and associative memory). These intentional test scores have been found to predict successful L2 morphosyntax learning especially when L2 learners receive explicit instruction/corrective feedback (e.g., Yalçin & Spada, 2016; Yilmaz & Granena, 2016)…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of studies have investigated the intricate connections between different types of aptitude and multiple aspects of L2 morphosyntax learning. In the context of EFL students in Turkey, for example, Yalçin and Spada (2016) found that those with higher language analysis abilities (grammatical inferencing) demonstrated strong gains in the acquisition of a relatively easy structure (past progressive) after 4 hr of instruction. Comparatively, those with higher memory abilities (associative memory) successfully acquired the relatively difficult structure (passive).…”
Section: Introductionmentioning
confidence: 99%